A positive electrode material containing polymer microspheres, and a preparation method and application thereof

By introducing polymer microspheres into the cathode material of lithium-ion batteries, the problems of complexity and high cost of existing technologies have been solved, and the lithium-ion transport efficiency has been improved, making it suitable for thick coatings and high-rate batteries.

CN122158551APending Publication Date: 2026-06-05PHYLION BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610537850.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-22
Publication Date
2026-06-05

AI Technical Summary

Technical Problem

Existing methods for improving lithium-ion transport efficiency in lithium-ion battery cathode materials are complex and costly, making them difficult to apply widely in industry.

Method used

Introducing polymer microspheres, especially expandable microspheres, into the cathode material of lithium-ion batteries can improve lithium-ion transport efficiency through existing production line processes such as slurry preparation, coating, baking, and rolling.

Benefits of technology

It significantly reduces ion transport impedance and improves lithium-ion transport efficiency. The capacity retention rate at 1C cycle at room temperature reaches 85%, and the discharge capacity at 3C rate reaches 91% of that at 1C. It is suitable for thick-coated and high-rate batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122158551A_ABST
    Figure CN122158551A_ABST
Patent Text Reader

Abstract

The application discloses a kind of high polymer microspheres containing positive electrode material and its preparation method and application.The application mixes raw materials including positive electrode active material, conductive agent, high polymer microspheres in dispersion medium, to obtain slurry;Then the slurry is coated on the current collector, and then baked and rolled to obtain lithium ion positive electrode.The application introduces high polymer microspheres into lithium ion battery positive electrode material for the first time, without synthesizing new materials, especially without changing the existing process of slurry coating, baking, rolling and assembling formation, without affecting the existing production line, with low cost, especially unexpectedly improving the lithium ion transmission efficiency: the discharge capacity is 91% of 1C at 3C rate, and the cycle capacity is maintained at 85% at room temperature 1C for 738 cycles, respectively increased by 10% and 23%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, specifically to an improved method for enhancing lithium-ion transport efficiency by introducing polymer microspheres into the cathode material slurry, applicable to thick-coated and high-rate lithium-ion batteries. Background Technology

[0002] Traditional lithium-ion battery cathode materials, under thick coating or high-rate charge / discharge conditions, are prone to increased polarization, capacity decay, and decreased cycle performance due to long lithium-ion transport paths and insufficient electrode porosity. Existing technologies typically improve electrode structure by optimizing the distribution of conductive agents. For example, by controlling the sintering temperature and time of manganese tetroxide (MnTe) to explore its grain boundary evolution and its regulatory mechanism on the performance of lithium manganese oxide electrodes, the grain boundary density and grain size distribution of MnTe under different sintering regimes and their impact on the cycle performance of lithium manganese oxide electrodes are analyzed. A specific sintering regime can induce the formation of high-density, small-angle grain boundaries, effectively suppressing electrode structure degradation and improving lithium-ion transport efficiency. For example, to improve the performance of LiNi… 0.6 Co 0.2 Mn 0.2 The cycling stability and rate performance of O2 (NCM622) cathode material under high voltage were investigated. Fluoroethylene carbonate (FEC) and lithium difluorophosphate (LiPO2F2) were introduced into the electrolyte, and batteries were assembled using these materials for systematic evaluation. The performance and mechanism of the modified batteries were studied in depth through electrochemical performance testing, microstructure characterization, and surface chemical analysis. Results showed that the Li / NCM622 half-cell using the dual-additive electrolyte improved capacity retention from 68.75% with the basic electrolyte to 91.25% after 150 cycles at 1C rate; the discharge specific capacity reached 138.2 mAh / g at a high current density of 5C. For example, to address the interfacial compatibility issues of sulfide-based electrolyte (Li6PS5Cl), high-nickel ternary cathode, and silicon-based anode, a four-layer structure model of "cathode-buffer layer-electrolyte-anode" was proposed. Through gradient concentration doping, nano-coating, and composite buffer layer design, the interfacial impedance was effectively reduced (from 85 Ω·cm). 2 Reduced to 28Ω·cm 2 This significantly improves lithium-ion transport efficiency and electrode stability. Experiments show that the optimized solid-state battery achieves an initial discharge specific capacity of 210 mAh / g at 0.1C (close to the theoretical value of 92%), and the capacity retention rate increases to 87% after 100 cycles. For example, a carbon nanotube / organic dye (CNT / PTCDA) composite porous nanofiber membrane lithium-ion battery cathode material was prepared by electrospinning. This composite porous nanofiber membrane exhibits excellent flexibility and electrochemical performance: at 10 mA g... -1 The specific capacity is as high as 113.2 mAhg. -1; in 2.0 Ag -1 The specific capacity remains at 37.5 mAhg. -1 Furthermore, at 0.2 Ag -1 After 200 cycles, it still retains 99% of its capacity. For example, Mg / Nb co-doped single-crystal LiNi was prepared by solid-state sintering. 0.9 Mn 0.1 O2 cathode material. By adjusting the doping ratio, it was found that the 1%Mg / 0.5%Nb doped sample exhibited excellent cycling stability under high voltage, with capacity retention rates of 83.1% and 67.3% at 4.3 V and 4.4 V, respectively. Although existing technologies have proposed various improvements to lithium-ion transport efficiency, the technical solutions employed are mostly complex, require rigorous chemical methods, or use high-cost raw materials, all of which limit their industrial application. Summary of the Invention

[0003] Existing technologies employ complex, demanding, and costly methods to improve lithium-ion transport efficiency, remaining largely theoretical and difficult to industrialize. This invention, for the first time, introduces polymer microspheres into lithium-ion battery cathode materials, eliminating the need to synthesize new materials and, more importantly, requiring no changes to existing processes such as slurry preparation, coating, baking, rolling, assembly, and capacity testing. It does not affect existing production lines and is cost-effective. Most notably, it unexpectedly improves lithium-ion transport efficiency: the discharge capacity at 3C is 91% of that at 1C, and the 1C cycle capacity at room temperature remains at 85% for 738 cycles, representing improvements of 10% and 23%, respectively.

[0004] The present invention adopts the following technical solution.

[0005] A positive electrode material containing polymer microspheres includes a positive electrode active material and a conductive agent, particularly including polymer microspheres.

[0006] This invention discloses a method for preparing the above-mentioned positive electrode material containing polymer microspheres, comprising the following steps: mixing raw materials including positive electrode active material, conductive agent, and polymer microspheres to obtain a positive electrode material containing polymer microspheres.

[0007] As is common knowledge, the positive electrode material containing polymer microspheres in this invention also includes conventional raw materials such as binders.

[0008] Furthermore, the mixing is carried out in a dispersion medium, which can be water or other conventional dispersion media used in the preparation of lithium-ion battery cathodes.

[0009] In this invention, the amount of polymer microspheres used is 0.1% to 1.3% of the weight of the cathode material; preferably, the amount of polymer microspheres used is 0.15% to 1.2% of the weight of the cathode material; preferably, the amount of polymer microspheres used is 0.2% to 1.1% of the weight of the cathode material; preferably, the amount of polymer microspheres used is 0.25% to 1.0% of the weight of the cathode material; preferably, the amount of polymer microspheres used is 0.3% to 0.9% of the weight of the cathode material, for example, the amount of polymer microspheres used is 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85% of the weight of the cathode material, or any percentage within the range.

[0010] In this invention, the amount of positive electrode active material is 90% to 96% of the weight of the positive electrode material; preferably, the amount of positive electrode active material is 91% to 95.5% of the weight of the positive electrode material; more preferably, the amount of positive electrode active material is 92% to 95% of the weight of the positive electrode material; for example, the amount of positive electrode active material is 93%, 93.5%, 94%, 94.5% of the weight of the positive electrode material, or any percentage within the range.

[0011] In this invention, the amount of conductive agent used is 1% to 5% of the weight of the positive electrode material; preferably, the amount of conductive agent used is 1.5% to 4.5% of the weight of the positive electrode material; more preferably, the amount of conductive agent used is 2% to 4% of the weight of the positive electrode material; for example, the amount of conductive agent used is 2.5%, 3%, 3.5% of the weight of the positive electrode material, or any percentage within the range.

[0012] In this invention, the weight of the positive electrode material does not include the weight of the dispersion medium. Preferably, the weight of the positive electrode active material, conductive agent, binder, and polymer microspheres is equal to the weight of the positive electrode material.

[0013] This invention discloses a lithium-ion cathode, comprising the above-mentioned cathode material containing polymer microspheres.

[0014] In this invention, the lithium-ion cathode also includes a current collector.

[0015] This invention discloses a method for preparing the aforementioned lithium-ion cathode, comprising the following steps: mixing raw materials, including a cathode active material, a conductive agent, and polymer microspheres, in a dispersion medium to obtain a slurry; then coating the slurry with a current collector, followed by baking and rolling to obtain the lithium-ion cathode. In this invention, the mixing, baking, and rolling processes are all existing methods, meaning that this invention can effectively improve the performance of lithium-ion batteries without altering existing production lines, making it suitable for industrial production.

[0016] This invention discloses a lithium-ion battery, comprising the above-mentioned positive electrode material containing polymer microspheres or a lithium-ion positive electrode.

[0017] Furthermore, lithium-ion batteries also include a separator, electrolyte, and negative electrode.

[0018] This invention discloses a method for preparing the above-mentioned lithium-ion battery, which includes the following steps: assembling a lithium-ion positive electrode, a separator, and a negative electrode, and then injecting an electrolyte to obtain a lithium-ion battery.

[0019] Furthermore, after injecting the electrolyte, the lithium-ion battery is subjected to formation and capacity testing.

[0020] In this invention, the electrolyte is a lithium salt solution containing ester solvent, used to dissolve the microsphere shell.

[0021] This invention discloses the application of the above-mentioned positive electrode material containing polymer microspheres or lithium-ion positive electrode in the preparation of lithium-ion batteries.

[0022] In this invention, the areal density of the lithium-ion battery cathode is greater than 500 g / m³. 2 Preferably, the positive electrode surface density is greater than 550 g / m³. 2 For example, the surface density of the positive electrode is greater than 600 g / m³. 2 Furthermore, the positive electrode surface density is greater than 650 g / m³. 2 .

[0023] This invention is the first to incorporate polymer microspheres into cathode materials. During high-temperature baking, these microspheres do not undergo side reactions with the cathode material and are uniformly distributed in the cathode coating. They maintain good distribution during rolling and swell and dissolve in the electrolyte, making them suitable for thick coatings (cathode surface density ≥ 600 g / m³). 2 It can significantly reduce ion transport impedance and improve lithium-ion transport efficiency, as well as high-rate (≥3C) batteries. Attached Figure Description

[0024] Figure 1 This is a photograph of the electrode sheet after baking in Example 1.

[0025] Figure 2 This is a photograph of the actual electrode sheet after rolling in Example 1.

[0026] Figure 3 The 3C rate curves are for Example 1 and Comparative Example 1.

[0027] Figure 4 The figures show the room temperature cycling curves for Example 1 and Comparative Example 1. Detailed Implementation

[0028] This invention provides a cathode material containing polymer microspheres and the lithium-ion cathode and battery prepared therefrom, achieved through the following steps: 1. Slurry preparation: The positive electrode active material (such as LiMn2O4), conductive agent (such as conductive carbon black), binder (such as PAA acrylic acid or CMC) and polymer microspheres are mixed in water to form a uniform slurry; 2. Coating and pre-baking: The slurry is coated onto the surface of the aluminum foil current collector, then heated and baked in a forced-air drying oven, and then rolled in a conventional manner to obtain the positive electrode of the lithium-ion battery; preferably, the heating and baking is carried out by pre-baking at 80-100°C for 5-15 minutes, and then baking at 130-200°C, preferably 150-170°C, for 10-60 minutes. 3. Battery Assembly: Assemble the positive electrode, polyethylene (PE) separator, and negative electrode into a battery. Inject electrolyte such as a carbonate solution containing LiPF6 (specific composition: LiPF6:LiFSI:LiBOB:EC:DMC=15:5:5:40:35, existing product) at 95°C for 24 hours. Let stand at room temperature to 40°C for 10 to 50 hours to obtain a lithium-ion battery. Perform conventional formation and capacity testing.

[0029] The raw materials used in this invention are all existing products that meet the conventional requirements for lithium-ion batteries. The polymer microspheres are preferably expandable microspheres, composed of a polymer shell and an encapsulated gas, such as UNICELL-PG07, with a particle size of 5-10 μm. These expand during high-temperature baking without causing side reactions with the positive electrode material, and are uniformly distributed in the positive electrode coating. They maintain good distribution during rolling and dissolve upon injection into the electrolyte without affecting electrode performance. This invention allows for the addition of small amounts of these materials to the positive electrode, making it suitable for thick coatings (area density ≥ 600 g / m³). 2 This invention provides high-rate (≥3C) batteries, significantly reducing ion transport impedance. The specific preparation procedures and performance testing employed in this invention utilize conventional techniques. Example 1

[0030] 1. Mix 94.5% LiMn2O4, 3% conductive carbon black, 2% PAA binder and 0.5% UNICELL-PG07 microspheres by mass percentage, and add deionized water to make a slurry; 2. Double-sided coating on aluminum foil, with an areal density of 660 g / m³. 2 Then preheat at 100°C for 10 minutes, and then bake at 160°C for 30 minutes; 3. The positive electrode sheet is obtained by rolling at room temperature, and then assembled with a graphite negative electrode and a polyolefin separator to form a square aluminum-shell lithium-ion battery. 1 mL of electrolyte (LiPF6+LiFSI+LiBOB / EC+DMC) is injected. Then, the battery is allowed to stand at 35℃ for 12 h. After formation and capacity testing, a 24 A h square lithium-ion battery is prepared.

[0031] Figure 1 The above-mentioned electrode sheet after baking is shown in a photograph, and no cracks are observed.

[0032] Figure 2 The above-mentioned roller-pressed electrode sheet is shown in a photograph, and no cracks are observed.

[0033] Comparative Example 1 Referring to Example 1, step 1 involves mixing 94.5% LiMn2O4, 3.25% conductive carbon black, and 2.25% PAA binder, and adding deionized water to form a slurry; the remaining materials and process steps are the same as in Example 1, and finally, the mixture is subjected to composition and capacity testing to prepare a 24Ah square lithium-ion battery.

[0034] Comparative Example 2 Referring to Example 1, in step 1, the UNICELL-PG07 microspheres were replaced with sodium bicarbonate, and the remaining materials and process steps were the same as in Example 1. Finally, the battery was tested for capacity and prepared to obtain a 24Ah square lithium-ion battery.

[0035] Comparative Example 3 Referring to Example 1, in step 1, the UNICELL-PG07 microspheres were replaced with activated carbon (a type of porous carbon with a specific surface area of ​​600 m² / g). The remaining materials and process steps were the same as in Example 1. Finally, the battery was tested for composition and capacity, and a 24Ah square lithium-ion battery was prepared.

[0036] Comparative Example 4 Referring to Example 1, in which step 1 the UNICELL-PG07 microspheres were replaced with mesoporous titanium dioxide, and the remaining materials and process steps were the same as in Example 1, the final step was to form a test capacity and prepare a 24Ah square lithium-ion battery.

[0037] Test Implementation Examples 1. Referring to Table 1, compared with Comparative Example 1, the average internal resistance of the lithium-ion battery cell in Example 1 is reduced by 30%, and it is also reduced compared with other additives.

[0038] 2. Figure 3 The figures show the 3C rate curves for Example 1 and Comparative Example 1. At 3C rate, the polarization of Example 1 is significantly less than that of Comparative Example 1, and its discharge capacity is higher. Calculations show that the discharge capacity of Example 1 at 3C rate is 91% of that at 1C rate, which is better than 83% of that of Comparative Example 1. This demonstrates that the present invention effectively improves rate performance and meets the requirements for high-flow-rate lithium-ion transport.

[0039] 3. Figure 4The table shows the room temperature cycling curves for Example 1 and Comparative Example 1. When the capacity remains at 85% during a 1C cycle at room temperature, Example 1 requires 738 cycles, while Comparative Example 1 requires 602 cycles, indicating a significantly faster capacity decay trend in Comparative Example 1. With a fixed percentage capacity decay, a higher number of cycles indicates better cycle performance and longer stable output. This also demonstrates that the present invention reduces the increased internal resistance caused by excessively high electrode compaction density, reduces polarization effects during charging and discharging, and alleviates material stress concentration caused by lithium-ion concentration gradients in thick electrodes during cycling, thereby suppressing capacity decay and improving cycle stability. This invention can be widely applied in power batteries, energy storage systems, and other fields, and is particularly suitable for high areal density lithium-ion batteries and fast-charging lithium-ion batteries.

[0040] Table 1. Average internal resistance of lithium-ion battery cells in comparative and example studies (10 cells per example) and battery performance.

[0041] Comparative Example 5 Referring to Example 1, 94.5% LiMn2O4, 3% conductive carbon black, 1% PAA binder and 1.5% UNICELL-PG07 microspheres were mixed by mass percentage, and deionized water was added to make a slurry. The rest were the same. The 24Ah square lithium-ion battery prepared had a discharge capacity retention rate of 81% at 3C relative to 1C.

[0042] Comparison Example The best-performing 24Ah square lithium-ion battery currently on the market, using LiMn2O4 as the positive electrode active material, conductive carbon black as the conductive agent, and LiPF6-based electrolyte, has a discharge capacity retention rate of 84% at 3C compared to 1C, and 639 cycles with a capacity retention of 85%.

[0043] Existing technologies for improving the performance of lithium active materials mostly employ methods that modify the positive electrode active material. Whether through coating, doping, or porosimetry, these methods are complex to prepare and increase costs, especially suffering from unstable or poor modification results. This is why mainstream lithium-ion batteries still use pure lithium materials as the positive electrode active material. This invention adopts a novel technical approach, without altering the existing active material, conductive agent, or binder of lithium-ion positive electrode materials—all conventional products. Performance verification shows that this invention, for the first time, incorporates polymer microspheres into the positive electrode material. During high-temperature baking, these microspheres do not undergo side reactions with the positive electrode material and are uniformly distributed in the positive electrode coating, maintaining good distribution during rolling. In particular, this method is simple, efficient, and suitable for mass production, providing a new approach for high-area-density and high-power lithium-ion batteries.

Claims

1. A positive electrode material containing polymer microspheres, comprising a positive electrode active material and a conductive agent, characterized in that, It also includes polymer microspheres.

2. The positive electrode material containing polymer microspheres according to claim 1, characterized in that, The amount of polymer microspheres used is 0.1% to 1.3% of the weight of the cathode material.

3. The method for preparing the positive electrode material containing polymer microspheres as described in claim 1, characterized in that, The process includes the following steps: mixing raw materials, including positive electrode active material, conductive agent, and polymer microspheres, to obtain a positive electrode material containing polymer microspheres.

4. A lithium-ion cathode, comprising the cathode material containing polymer microspheres as described in claim 1.

5. The method for preparing the lithium-ion cathode according to claim 4, characterized in that, The process includes the following steps: mixing raw materials, including positive electrode active material, conductive agent, and polymer microspheres, in a dispersion medium to obtain a slurry; then coating the slurry with a current collector, followed by baking and rolling to obtain a lithium-ion positive electrode.

6. A lithium-ion battery, comprising the positive electrode material containing polymer microspheres as described in claim 1 or the lithium-ion positive electrode as described in claim 4.

7. The lithium-ion battery according to claim 6, characterized in that, It also includes the diaphragm, electrolyte, and negative electrode.

8. The method for preparing the lithium-ion battery according to claim 7, characterized in that, The process includes the following steps: assembling a lithium-ion positive electrode, a separator, and a negative electrode, and then injecting an electrolyte to obtain a lithium-ion battery.

9. The application of the cathode material containing polymer microspheres as described in claim 1 or the lithium-ion cathode as described in claim 4 in the preparation of lithium-ion batteries.

10. The application of the lithium-ion battery of claim 6 in the preparation of power supply materials.